Answer:
k = 20
Step-by-step explanation:
t1 = a = k-4
a = k - 4
t2 = ar = k
(k-4)r = k - 4
r = k/(k-4)
t3 = ar^2 = k + 5
(k - 4)(k/k - 4)^2 = k+5
k^2/k-4 = k+5
k^2 = (k+5)(k-4)
k^2 = k^2 -4k +5k -20
0 = k -20
k =20
1. 2x - (3x + 6).....negative before parentheses makes everything inside parentheses opposite
2. 2x - 3x - 6....2x - 3x = -1x
3. -1x - 6
Answer:
-1x - 6
Answer:
2x-3
Step-by-step explanation:
f(x) = 3x-1
g(x) = x+2
Find (f-g)(x), this means we need to subtract g from x.
(3x-1) - (x+2)
Subtract the like terms:
3x -x = 2x
-1 -2 = -3
Combine them to get 2x-3
I don't know what 22/7 is about. However, 28*2*3.14 is your answer. So ~175 feet